Does enhanced insulin sensitivity improve sleep measures in patients with obstructive sleep apnea: A randomized, placebo-controlled pilot study - Liu, Alice (Sleep Med, 2016)
BACKGROUND: High fasting insulin levels have been reported to predict development of observed apneas, suggesting that insulin resistance may contribute to the pathogenesis of obstructive sleep apnea (OSA). The study aim was to determine whether enhancing insulin sensitivity in individuals with OSA would improve sleep measures. PATIENTS/METHODS: Insulin-resistant, nondiabetic individuals with untreated OSA were randomized (2:1) to pioglitazone (45mg/day) or placebo for 8 weeks in this single-blind study. All individuals had repeat measurements pertaining to sleep (overnight polysomnography and Functional Outcomes of Sleep Questionnaire) and insulin action (insulin suppression test). RESULTS: Forty-five overweight/obese men and women with moderate/severe OSA were randomized to pioglitazone (n=30) or placebo (n=15). Although insulin sensitivity increased 31% among pioglitazone-treated as compared to no change among individuals receiving placebo ((p<0.001 for between-group difference), no improvements in quantitative or qualitative sleep measurements were observed. CONCLUSIONS: Pioglitazone administration increased insulin sensitivity in otherwise untreated individuals with OSA, without any change in polysomnographic sleep measures over an 8-week period. These findings do not support a causal role for insulin resistance in the pathogenesis of OSA.